Use of Profit and Cash Flows in Predicting Financial Distress Food and Beverage Companies - Dian Efriyenty; Neni Marlina Br Purba (Owner : Riset dan Jurnal Akuntansi, 2022)
In recent years there have been several companies experiencing financial difficulties. If the state of a company continues to experience financial difficulties, the company can go bankrupt if it does not immediately find a solution. Several companies have experienced unstable profits in the last 3 years. Even a very insignificant increase in profit. There can even be a drastic drop in profits for food and beverage companies. Ultra Milk Company also experienced a drastic decline in profits until 2019 to 1,030,191. And the purpose of this study is to see the profit and increase in cash have an impact on financial difficulties. This research is for purposeful sampling of 10 companies for data from the last 5 years. Testing of this research from testing alone and simultaneously. The data collected was then analyzed by quantitative methods. The results of the study of earnings testing have an effect on financial difficulties, while cash flows have an effect on financial difficulties. However, to be tested simultaneously, namely profit and increase in cash flow, it has an impact on financial difficulties. The result of this financial difficulty can trigger the company to go bankrupt. So that bankruptcy greatly triggers a decrease in the level of business profits.